P265 Linking dysfunctional premotor-to-motor connectivity to disease severity of obsessive–compulsive disorder – A robotic dual-site TMS study. Issue 3 (March 2017) - Raffin, E.; Harquel, S.; Passera, B.; Favre, P.; Siebner, H.R.; David, O.; Polosan, M.
Abstract : Introduction: There is evidence that the right Inferior Frontal Gyrus (IFG) exerts an inhibitory influence over the left primary motor cortex (M1) when actions need to be inhibited. Patients with obsessive–compulsive disorder (OCD) present deficient motor inhibition and attentional control. We therefore hypothesized that in patients with OCD, inhibitory inter-hemispheric IFG-M1 connectivity might be impaired in proportion with clinical severity. Method: We used dual-site neuronavigated TMS to probe resting-state IFG-M1 connectivity in 12 OCD patients and 20 healthy volunteers. A conditioning stimulus controlled by a TMS robot, was delivered over the right IFG at latencies ranging from of −0.3 to 20 ms prior to a suprathreshold test stimulus applied to the left M1. Results: A repeated measure ANOVA on the normalized MEPs showed a significant main effect of the inter-stimulus interval (ISI) between the conditioning and test stimuli ( p = 0.02) and a marginal Group (patients vs. controls) effect ( p = 0.065). In controls, we found two reverberant inhibitory peaks at an ISI of 8 ms. In patients, the IFG-M1 inhibition only peaked at 8 ms with significant reduced cortico-cortical inhibition. Stepwise regression analysis revealed that the compulsion sub-score of the YBOCS predicted deficient IFG-M1 inhibition in OCD patients. Discussion: Our finding that reduced resting-state IFG-M1 inhibition is positively associated with obsession severity points to a significant role of abnormal cortico-cortical premotor-to-motor connectivity in the pathophysiology of OCD.